Microwave generation in system with virtual cathode; Proceedings of the 6th International Conference on High-power Particle Beams, June 9-12, 1986, Interantional Confence Sic Center, Kobe, Japan - Didenko A. N.; Zherlitsin A. G.; Kuznetsov S. I. Sergey Ivanovich; Melnikov G. V.; Filipenko N. M.; Fomenko G. P. (1986, 1986)
В фонде НТБ ТПУ отсутствует